2008
DOI: 10.1007/s11199-008-9431-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Impact of Bullying and Sexual Harassment Victimization on the Mental and Physical Health of Adolescents

Abstract: A sample of 522 middle and high school students from a school district in a northeastern state in the U.S. was used to address two questions about bullying and sexual harassment: Is one more frequent than the other, and are there gender or sexual orientation differences in this regard? And, does one have greater adverse health effects than the other, and, if so, for whom? Bullying occurred more frequently than sexual harassment for both girls and boys but not among sexual minorities. Girls were bullied or hara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
203
3
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 231 publications
(233 citation statements)
references
References 43 publications
14
203
3
5
Order By: Relevance
“…The adjusted R 2 values provided further evidence of differences: The values were higher for girls than boys on all five outcomes. In an earlier study, we found significant relationships between peer victimization-sexual harassment in particular-and health outcomes (Gruber & Fineran, 2008). In this article, we found that peer victimization-especially sexual harassment-alienated students from school, undermined their relationships with teachers, and adversely affected their grades.…”
Section: The Harm Of Peer Victimization: Summary Of Findingsmentioning
confidence: 61%
“…The adjusted R 2 values provided further evidence of differences: The values were higher for girls than boys on all five outcomes. In an earlier study, we found significant relationships between peer victimization-sexual harassment in particular-and health outcomes (Gruber & Fineran, 2008). In this article, we found that peer victimization-especially sexual harassment-alienated students from school, undermined their relationships with teachers, and adversely affected their grades.…”
Section: The Harm Of Peer Victimization: Summary Of Findingsmentioning
confidence: 61%
“…Furthermore, other scholars have shown that sexual harassment at school is part of everyday life [4446] and that sexual harassment victimisation is associated with poor mental health outcomes [29,31,32]. Hence, preventing sexual harassment victimisation seems to be important as a factor to consider when planning interventions to support girls’ positive mental health development.…”
Section: Discussionmentioning
confidence: 99%
“…Psychosocial variables were sexual harassment victimization, bullying victimisation and peer support. Respondents were asked about sexual harassment victimisation using an instrument previously used by Gruber and Fineran [31,32] and the AAUW study [33], by indicating how often they had experienced the following behaviours against their will during the past 6 months (never, once, a few times, many times): touched, grabbed or pinched you in a sexual manner; pushed you into a corner in a sexual manner; spread sexual rumours about you; commented on you, made a joke out of you or gesticulated in your direction in a sexual manner; looked at you in a manner that felt intrusive and sexual; shown or left you sexual images, photos or drawings; written sexual messages about you on bathroom walls or in locker rooms; called you a lesbian, fag or such words; pulled/pulled off your clothes in a sexual manner (e.g. pulled your bra straps, pulled your underwear or pulled up your skirt); tried to kiss or hug you; called you a “4 letter word”; commented on your looks, your body or your personal life in a sexual manner; spread comments about you or pictures of you on mobile phones; publicly commented on how attractive or unattractive you are.…”
Section: Design Procedures and Participantsmentioning
confidence: 99%
“…While most of these survey studies employed quantitative research methods (Birkett, Espelage, & Koenig, 2009;Espelage, Aragon, Birkett, & Koenig, 2008;Gruber & Fineran, 2008;Murdock & Bolch, 2005;Poteat, Espelage, & Koenig, 2009;Sandfort, Bos, Collier, & Metselaar, 2010;Walls, Kane, & Wisneski, 2010;Wilkinson & Pearson, 2009), a few employed qualitative methods (Adelman & Woods, 2006). Prior to 2010, qualitative studies that did not rely on surveys as the primary data source were less prevalent in the field overall, and most focused on the individual experiences or beliefs of educators (Dessel, 2010;McCabe & Rubinson, 2008;Payne & Smith, 2010;Tooms, 2007;Zach, 2010), while a smaller segment of studies focused on the experiences of LGBTQ youth (Davidson, 2009;Lee, 2002;Russell, Muraco, Subramaniam, & Laub, 2009;Savin-Williams, 2005).…”
Section: Sampling Strategy and Selection Criteriamentioning
confidence: 99%
“…These studies are a sampling of the myriad survey studies from the last decade that have found correlations between the prevalence of interpersonal discrimination and the negative experiences of LGBTQ youth (Advocates for Children, Inc., 2005;Espelage et al, 2008;Gruber & Fineran, 2008;Morrison & L'Heureux, 2001;Murdock & Bolch, 2005;Poteat et al, 2009;Russell, Seif, & Truong, 2001;Sandfort et al, 2010;Walls et al, 2010;Wilkinson & Pearson, 2009). All of the studies that employ this frame identify the problem facing…”
Section: Onward: Lgbtq Youth As Victimsmentioning
confidence: 99%